A mesoporous nanocontainer gated by a stimuli-responsive peptide for selective triggering of intracellular drug release. Issue 15 (29th March 2016) - Lee, Jeonghun; Oh, Eun-Taex; Yoon, Haerry; Kim, Hyunmi; Park, Heon Joo; Kim, Chulhee
Abstract : Peptide gatekeepers with a capability of stimuli-responsive conformational conversion were designed to precisely control the release of an entrapped drug in a mesoporous nanocontainer, which selectively induced apoptosis in a controlled manner not in normal CCD but in A549 cells. Abstract : Mesoporous silica nanocontainers (MSNs) with biologically responsive gatekeepers have great potential for effective delivery of cargo molecules to the desired sites. For that purpose, peptides could be effective candidates as gatekeepers because of their bioresponsiveness and targeting capability. Taking advantage of the zinc finger domain peptide (CXXC), we designed a biocompatible all-peptide gatekeeper (WCGKC) with on–off gatekeeping capability through stimulus-responsive conformational conversion and the steric bulkiness of the tryptophan unit. The turn structure induced by an intramolecular disulfide bond of the peptide gatekeeper (WCGKC-SS) completely inhibited the release of the entrapped doxorubicin (DOX). However, upon reduction of the disulfide bond by glutathione (GSH), the peptide conformation was converted to a random structure, which opened the orifice of the mesopore leading to the release of DOX. The amine moiety of the lysine of the peptide gatekeeper was PEGylated to enhance dispersion stability and biocompatibility of the nanocontainer. Furthermore, the MSNs with the peptide gatekeeper (PEG-WCGKC-SS-Si) selectively released the entrapped DOX in A549 human lung cancer cells in a controlled manner triggered by intracellular GSH, but not in CCD normal lung cells containing a low intracellular GSH level. In A549 cells, DOX-loaded PEG-WCGKC-SS-Si exhibited about 10-times higher cytotoxicity induced by apoptosis than that in CCD cells.